2021
DOI: 10.3390/jcm10194547
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Management of Chronic Thromboembolic Pulmonary Hypertension in Greece. Real-World Data from the Hellenic Pulmonary Hypertension Registry (HOPE)

Abstract: Chronic Thromboembolic Pulmonary Hypertension (CTEPH) is a rare disease with poor prognosis if left untreated, characterized by pulmonary vascular bed obstruction due to unresolving thromboembolic material. The Hellenic pulmonary hypertension registry (HOPE) was launched in Greece in early 2015 and enrolls patients from all pulmonary hypertension subgroups in Greece. In total, 98 patients with CTEPH were enrolled from January 2015 until November 2019. Of these patients, 55.1% represented incident population, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…These data highlight the natural history of CTEPH, which appears as a potential long-term complication of one or more thromboembolic events [11][12][13][14]. However, why only a minority of patients (cumulative incidence 0.1-9.1%) may develop PH after an initial episode of PE remains to be clarified [13][14][15][16]. Some epidemiological studies have identified some predisposing factors offering some insight as to the etiology of CTEPH [17][18][19].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…These data highlight the natural history of CTEPH, which appears as a potential long-term complication of one or more thromboembolic events [11][12][13][14]. However, why only a minority of patients (cumulative incidence 0.1-9.1%) may develop PH after an initial episode of PE remains to be clarified [13][14][15][16]. Some epidemiological studies have identified some predisposing factors offering some insight as to the etiology of CTEPH [17][18][19].…”
Section: Introductionmentioning
confidence: 91%
“…As aforementioned, CTEPH is a potentially treatable disease, and the treatment of choice is pulmonary endarterectomy (Figure 3) [12,13,38,39]. This procedure involves a bilateral endarterectomy of the pulmonary arteries with the removal of the obstructive thromboembolic material from the vessel wall.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Demerouti et al, provide detailed data on Greek CTEPH patients between 2015 and 2019. Ιn total, 98 patients were enrolled; differences between operable and non-operable CTEPH patients in real world are presented [ 13 ]. Finally, Karyofyllis et al, provide data from 180 BPA procedures performed in Greece.…”
mentioning
confidence: 99%